Analysis of Financing Risk Management Implementation at Baitul Maal Wat Tamwil - Ainu Nadina; Ferry Khusnul Mubarok; Yuli Haryati (AL-ARBAH: Journal of Islamic Finance and Banking, 2022)
AbstractPurpose - This study aims to analyze the implementation of financing risk management in Sharia Cooperatives at BMT UAS Pamotan.Method - The method uses a qualitative approach, using primary data from interviews with the finance staff and reading from various references.Result - The implementation of financing risk management at BMT UAS Pamotan is through two approaches, namely internal and external. Internal approach by anticipating various possible risks, namely through management audits and evaluations. Meanwhile, externally through service maximization, and tightening 5C (Character, Capacity, Capital, Collateral, and Conditions).Implication - There needs to be a closer method between the BMT and partners (customers) so that the possibility of financing risks arising can be minimized.Originality- Analyzing qualitatively related to existing financing in Islamic microfinance institutions.